Integration of magnetic properties and heavy metal chemistry to quantify environmental pollution in urban soils, Kathmandu, Nepal - Gautam, Pitambar; Blaha, Ulrich; Appel, Erwin (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp.140-1